Cyril of Jerusalem - Yarnold, Edward; Cyril, Saint, Bishop of Jerusalem, approximately 315-386. (London ; New York : Routledge, 2000)
This study of the life and works of Cyril, Bishop of Jerusalem, assesses Cyril's thought in the context of fourth-century theological developments and includes up-to-date translations of a selection of his writings.
Introduction: Cyril's life -- Jerusalem -- Works -- Liturgy -- Cyril's use of scripture, and his theology -- Translation: Texts -- Letter to Constantius -- Homily on the Paralytic by the pool -- Procatechesis -- Catecheses -- Catechesis 3, 4, 5, 6, 10, 11, 12, 13, 14, 18 -- Mystagogic catechesis 1, 2, 3, 4, 5.
Includes bibliographical references (pages 206-208) and index.
Print version record.
Master record variable field(s) change: 600
Keywords: Cyril, -- Saint, Bishop of Jerusalem, -- approximately 315-386.; Cyril, -- Saint, Bishop of Jerusalem, -- approximately 315-386; Theology -- Early works to 1800.; Theology; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Theology; Teologi -- Teologi; Electronic books; Early works